2022
DOI: 10.3389/fmars.2021.741620
|View full text |Cite
|
Sign up to set email alerts
|

Water Temperature at Different Depths Affects the Distribution of Neon Flying Squid (Ommastrephes bartramii) in the Northwest Pacific Ocean

Abstract: Ommastrephes bartramii can vertically swim during its life, and previous studies have suggested the need to account for preferred habitat distribution influenced by water temperatures at different depths. To explore the impacts of deep-water temperature on O. bartramii spatial distribution, we constructed generalized additive models (GAMs) based on the Chinese squid-jigging fishery data and the Argo deep water temperature data during 2005–2018 in the Northwest Pacific Ocean to analyze the relationships between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…These El Niño/La Niña events affect the Kuroshio-Oyashio transition area through the temperature dynamics that modulated by the Kuroshio transport [24]. According to previous studies, the optimal ranges of the SST for suitable habitat area of Ommastrephes bartramii ranged between 15-20 • C [3,11,39]. In our study, the isothermal lines for 15 8).…”
Section: Influence Of El Niño/la Niña Events On the Distribution Of F...mentioning
confidence: 49%
See 3 more Smart Citations
“…These El Niño/La Niña events affect the Kuroshio-Oyashio transition area through the temperature dynamics that modulated by the Kuroshio transport [24]. According to previous studies, the optimal ranges of the SST for suitable habitat area of Ommastrephes bartramii ranged between 15-20 • C [3,11,39]. In our study, the isothermal lines for 15 8).…”
Section: Influence Of El Niño/la Niña Events On the Distribution Of F...mentioning
confidence: 49%
“…It has been found that the distribution of squid is influenced by the vertical distribution of seawater temperatures in the North Pacific [3] and that warm eddies during periods of instability in the Kuroshio contribute to the formation of high squid production areas [6]. However, to understand the relationship between squid distribution, eddies and the Kuroshio, more research is needed to achieve quantitative analysis through modelling studies, e.g., adding the Kuroshio index as a factor in the model.…”
Section: Impact Of the Kuroshio On The Distribution Of Fishing Groundsmentioning
confidence: 99%
See 2 more Smart Citations
“…The SSTB is a crucial environmental component that significantly impacts the distribution, behavior, and ecological dynamics of squid. Studying the correlation between the temperature of the ocean floor and squid may provide significant knowledge for the management of fisheries, conservation initiatives, and forecasts of how squid populations would react to changes in environmental circumstances (Wang et al, 2022). Notably, temperature changes influence the growth and development of the squid reproductive system (Boavida-Portugal et al, 2010;Wang et al, 2013;Pang et al, 2020).…”
Section: Figurementioning
confidence: 99%